PERBEDAAN ATHEROSIS PLASENTA ANTARA PREEKLAMPSIA RINGAN DAN PREEKLAMPSIA BERAT DI RUANG BERSALIN BADAN PELAYANAN KESEHATAN RUMAH SAKIT UMUM DR.WAHIDIN SUDIRO HUSODO MOJOKERTO - Ratnaningsih, Tri (JURNAL KEPERAWATAN BINA SEHAT, 2010)
Preeclampsia is one factor of the increased morbidity and maternal and perinatal mortality. The cause of preeclampsia up to now unclearThe purpose of this study was to prove the existence of differences in the incidence of placenta atherosis between mild and severe preeclampsia preeclampsia.The design of this study using observational studies to make observations during (cross-sectional). In this study of a population of pregnant women who met the inclusion criteria and do not have the factors contained in the exclusion criteria, were selected preekampsia group with mild and severe preeclampsia. Each - each placenta during childbirth taken Histopathological examination to see their atherosis placenta. Research conducted at the maternity room BAPELKES Hospital Dr Wahidin Sudirohusodo Mojokerto, by the time the study between March 2008 until the end of July 2008. The population of this study were pregnant women with severe pregnancy complications Preekampsia more than 20 weeks and pregnant women with mild preeclampsia with age more than 20 weeks gestation. Sample selection is done by consecutive sampling. Data were analyzed by Chi-Square test to compare the number of atherosis placenta in PER and PEB with significance level of 95% ((ρ <0.05).The Results of this study, the difference atherosis fetal placental layers on mild preeclampsia and severe preeclampsia is based on Mann-Whitney test showed calculation results ρ = 0.003, meaning that the number atherosis on the fetal side of the placenta there is mild preeclampsia is less than the amount of weight atherosis placenta in preeclampsia. Differences atherosis middle layer of the placenta in preeclampsia mild and severe preeclampsia based on test T-test that shows the calculation results ρ = 0.035, meaning that the number of placental atherosis no side amid the mild preeclampsia is less than the amount of weight atherosis placenta in preeclampsia. Atherosis difference maternal placental layers on mild preeclampsia and severe preeclampsia based on test T-test that shows the calculation results ρ = 0.005, meaning that the number atherosis there placenta in preeclampsia mild maternal side is less than the amount of weight atherosis placenta in preeclampsia. The total sum atherosis placenta showed ρ = 0.001. This proves that there is a significant difference between the number of atherosis placenta in mild and severe preeclampsia.Acute Atherosis placenta is a typical symptom that occurs in the fetuses of mothers who suffer preelampsia.Keywords: Atherosis, mild preeclampsia, severe preeclampsia, Histopathology